2017
DOI: 10.1021/acs.inorgchem.7b00253
|View full text |Cite
|
Sign up to set email alerts
|

Subtle Structural Changes in (CuIIL)2MnII Complexes To Induce Heterometallic Cooperative Catalytic Oxidase Activities on Phenolic Substrates (H2L = Salen Type Unsymmetrical Schiff Base)

Abstract: A new Cu(II) complex of an asymmetrically dicondensed Schiff base (HL = N-(2-hydroxyacetophenylidene)-N'-salicylidene-1,3-propanediamine) derived from 1,3-propanediamine, salicylaldehyde, and o-hydroxyacetophenone has been synthesized. Using this complex, [CuL] (1), as a metalloligand, two new trinuclear Cu-Mn complexes, [(CuL)Mn(N)(HO)](ClO)·HO (2) and [(CuL)Mn(NCS)] (3), have been prepared. Single-crystal structural analyses reveal that complexes 2 and 3 both have the same bent trinuclear {(CuL)Mn} structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 94 publications
4
86
1
Order By: Relevance
“…Though this Schiff base ligand ( L ) actually behaves as a polydentate ligand but all the donor centres are not employed in the formation of Zn(II) complex. Previously it was seen that this ligand acted as an important backbone for making hetero‐metallic clusters (3d–4f) which led to important magnetic properties ,. In this present case, this particular ligand actually displays selectivity towards Zn(II) ion and for this reason it is observed that methoxy‐O (O3 & O4) and alkoxy‐O (O6) remains unemployed in the structural building,…”
Section: Resultsmentioning
confidence: 47%
“…Though this Schiff base ligand ( L ) actually behaves as a polydentate ligand but all the donor centres are not employed in the formation of Zn(II) complex. Previously it was seen that this ligand acted as an important backbone for making hetero‐metallic clusters (3d–4f) which led to important magnetic properties ,. In this present case, this particular ligand actually displays selectivity towards Zn(II) ion and for this reason it is observed that methoxy‐O (O3 & O4) and alkoxy‐O (O6) remains unemployed in the structural building,…”
Section: Resultsmentioning
confidence: 47%
“…Complex 1 consists of a square‐planar coordinated structure around a central metal ion [Cu 2+ ] and a completely symmetric decahedron of boron. In the symmetric unit, four coordinated alkylimidazole N atoms constituted the basal plane around Cu 2+ . There are fewer contacts between the C atoms and the N atoms in the different ligands.…”
Section: Resultsmentioning
confidence: 99%
“…6). Relatively few coordination complexes, or polymers, have been reported showing this type of Cu 2 O 2 rhombic cluster [29][30][31][32][33][34]. The Cu centers are fivecoordinated and surrounded by three oxygen atoms from two mal ligands and two nitrogen atoms from one 4dmb ligand.…”
Section: Crystal Structure Ofmentioning
confidence: 99%